Designing and implementing a real estate appraisal system: The case of Québec Province, Canada. (March 2015) - Kettani, Ossama; Oral, Muhittin
Abstract: Real estate appraisal is of great importance to several socio-economic stakeholders for different reasons and justifications: local governments and municipalities for taxation purposes; banks for mortgage and other credit applications processing; property valuation companies for marketing activities; and property developers and investors for sound investment decision-making. This paper summarizes the real estate appraisal system that has been developed for and with CUQ (Coomunaité urbaine de Québec), CUM (Communaité urbaine de Montréal), and Communaité urbaine de Gatineau (CUG) and implemented over the last twenty years in the Province of Québec. The salient features of the property appraisal system are: (1) property-specific individual appraisal using a new regression method called "analogical regression", (2) mass-appraisal based on property-specific individual appraisals, and (3) the size of real estate coverage (over 1, 050, 000 properties) and the variety of real estate profiles considered (shopping centers, office buildings, residential properties, farms, industrial units, etc.).